1978
DOI: 10.1029/jb083ib02p00798
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the East Pacific Rise crest from multichannel seismic reflection data

Abstract: Computer‐processed multichannel seismic reflection profiles from the crestal zone of the East Pacific Rise near the Siqueiros Fracture Zone have revealed distinct layering in the structure not previously observed in single‐channel reflection records. After processing, which included common depth point gathering, normal move‐out and stack, time‐varying predictive deconvolution, and wave equation migration, three distinct crustal layers emerge as coherent events across the rise crest. The base of the third layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 11 publications
0
34
0
Order By: Relevance
“…Shallow and deep intracrustal events (e.g. Musgrove and Austin, 1983;Mutter and NAT Study Group, 1985;McCarthy et al, 1988;Rohr et al, 1988), proposed magma chamber reflection events (Herron et al, 1978;Hale et al, 1982;Detrick et al, 1987;Rohr et al, 1988), and Moho reflections (e.g. Stoffa et al, 1980;Mutter and NAT Study Group, 1985) have been identified.…”
Section: Range (Kms)mentioning
confidence: 99%
“…Shallow and deep intracrustal events (e.g. Musgrove and Austin, 1983;Mutter and NAT Study Group, 1985;McCarthy et al, 1988;Rohr et al, 1988), proposed magma chamber reflection events (Herron et al, 1978;Hale et al, 1982;Detrick et al, 1987;Rohr et al, 1988), and Moho reflections (e.g. Stoffa et al, 1980;Mutter and NAT Study Group, 1985) have been identified.…”
Section: Range (Kms)mentioning
confidence: 99%
“…However, even on the East Pacific Rise, which has a high magmatic budget such models have been known for some while to be inconsistent with seismological observations. Early refraction experiments on the EPR [Orcutt et al, 1975[Orcutt et al, , 1976Rosendahl et al, 1976] detected a low-velocity zone whose top coincided with an upper crustal reflector [Herron et al, 1978[Herron et al, , 1980Hale et al, 1982] which was interpreted to be the roof of a magma chamber. However, the vertical extent and velocities of the low-velocity anomaly detected by the refraction experiments were not consistent with a very magma body.…”
Section: The Axial Low-q Regionmentioning
confidence: 99%
“…The East Pacific Rise at 9*30'N has been the site of many targeted studies of in seismology [Orcutt et al, 1976;Herron et al, 1978;Detrick et al, 1987;Vera et al, 1990;Toomey et al, 1990a;Christeson et al, 1991a, b], bathymetry [Macdonald et al, 1984Wilcock et al, 1992], petrology [Langmuir et al, 1986], gravity [Madsen et al, 1990], high-resolution imaging , and magnetics . Indeed, the large number of observational constraints led Sinton and Detrick [1992] to base their model for magma chambers on fast-spreading ridges on this locality.…”
Section: Pacific Risementioning
confidence: 99%
“…(Orcutt et aI, 1975;Rosendahl et al, 1976;Reid et al, 1977;Herron et al, 1978). Rosendahl (l976) and Lonsdale (l977a) suggested that the edge of the magma chambers coincides with the beginning of large scale relief at.…”
mentioning
confidence: 99%